Left ventricular remodeling and function after transapical versus transfemoral transcatheter aortic valve replacement. Issue 5 (27th January 2019) - Al‐Hijji, Mohammed A.; Zack, Chad J.; Nkomo, Vuyisile T.; Pislaru, Sorin V.; Pellikka, Patricia A.; Reeder, Guy S.; Greason, Kevin L.; Rihal, Charanjit S.; Eleid, Mackram F.
Abstract: Background: The effect of utilizing transapical (TA) access for transcatheter aortic valve replacement (TAVR) on cardiac function has not been well studied. Aims: The aim of this retrospective study is to determine the direct effects of TA access for TAVR on myocardial function parameters and their correlation with 4‐year survival. Methods: Three hundred and thirty propensity matched patients, who underwent TAVR using Sapien valve (Edwards Lifesciences Corp, Irvine, CA) between February 15, 2012 and June 17, 2016 (115 TA and 115 transfemoral [TF] routes) were studied. The pre‐ and 1 month post‐TAVR echocardiographic features of both groups were compared. The 4‐year survival in both groups was analyzed. Results: Baseline clinical characteristics, diastolic function parameters, left ventricular (LV) chamber size, and ejection fraction were similar between matched TA and TF groups. At 1 month following TAVR, there was a significant increase in stroke volume index (SVI) in both TA (mean increase 7 cm 3 /m 2 ; P = 0.03) and TF groups (mean increase 7 cm 3 /m 2 ; P < 0.001). Left ventricular ejection fraction (LVEF) significantly increased post TF TAVR (mean increase 2%; P = 0.008), but no significant increase was observed post TA TAVR (mean increase 1%; P = 0.27). Both groups had significant improvement in aortic valve (AV) hemodynamics post‐TAVR ( P < 0.001). Overall, there were no significant differences in the mean change of SVI, LVEF, or left ventricular end diastolic dimensions (LVEDDs) post TA versus TF TAVR. There was no significant difference in 4‐year survival in the TF compared to TA group (49% vs 50%, P = 0.43). Conclusion: Both TA and TF TAVR were equally associated with favorable changes in LV SVI and AV hemodynamics in 30 days. TA TAVR patients had similar 4 year survival to propensity matched TF TAVR; therefore, TA TAVR remains an acceptable alternative access route in patients not amenable to TF TAVR.